Molecular beam epitaxial growth and characterization of Al(Ga)N nanowire deep ultraviolet light emitting diodes and lasers. (17th August 2016) - Mi, Z; Zhao, S; Woo, S Y; Bugnet, M; Djavid, M; Liu, X; Kang, J; Kong, X; Ji, W; Guo, H; Liu, Z; Botton, G A
Abstract: We report on the detailed molecular beam epitaxial growth and characterization of Al(Ga)N nanowire heterostructures on Si and their applications for deep ultraviolet light emitting diodes and lasers. The nanowires are formed under nitrogen-rich conditions without using any metal catalyst. Compared to conventional epilayers, Mg-dopant incorporation is significantly enhanced in nearly strain- and defect-free Al(Ga)N nanowire structures, leading to efficient p -type conduction. The resulting Al(Ga)N nanowire LEDs exhibit excellent performance, including a turn-on voltage of ̃5.5 V for an AlN nanowire LED operating at 207 nm. The design, fabrication, and performance of an electrically injected AlGaN nanowire laser operating in the UV-B band is also presented.